A methodology for quantitative vulnerability assessment of coupled multi-hazard in Chemical Industrial Park. (March 2019) - Chen, Guohua; Huang, Kongxing; Zou, Mengting; Yang, Yunfeng; Dong, Haoyu
Abstract: Natural disasters triggered technological (Na-Tech) events are low probability but high impact events. The cascading effects occur frequently under the impact of coupled natural disasters and industrial accidents in Chemical Industrial Park (CIP), which exacerbates the vulnerability of CIP. Therefore, it's essential to carry out the coupled multi-hazard vulnerability assessment in CIP. In the present study, a new methodology involving quantitative vulnerability assessment model and partition technology is proposed to assess the regional vulnerability. Considering the characteristics of multi-hazard, the vulnerability theory in CIP is explored, including sensitivity, resilience and exposure. Furthermore, the quantitative vulnerability assessment model for coupled multi-hazard is put forward based on cellular automata (CA) theory. Combined the model with GIS technology, the vulnerability partition technology is developed and the results of the vulnerability assessment can be visualized. The case study in a national CIP located at the coastal area of Southern China evidenced that the coupled multi-hazard vulnerability is much larger than the single-hazard and the validity of the result is verified by graph theory. Therefore, the methodology proposed can be applied to vulnerability assessment within an industrial park level and used to support the decision-making of regional planning, emergency management, disaster prevention and mitigation for CIP. Highlights: The vulnerability theory of coupled multi-hazard in CIP has been analyzed. A methodology for quantitative vulnerability assessment of coupled multi-hazard in CIP has been put forward. The partitioning platform based on CA-GIS has been developed, which can realize visualization of the results. The methodology put forward can truly be applied to real-life CIP containing hundreds of factories and installations.